PELAKSANAAN FUNGSI LEGISLATIF - M. Yusuf Habibi E.21108120 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Writing this article is intended to provide an understanding of the role of leader in the Kapuas Hulu Regency Legislative Function Implementation. Problem of Kapuas Hulu Regency leadership is not able to fully demonstrate the behavior of a leader who can move the members in carrying out legislative duties. Through the writing of this article is also intended, so abilities Kapuas Hulu Regency leadership in mobilizing its members to carry out legislative functions can be implemented, in terms of the leadership of Parliament SCARA attention to the needs of members in providing motivation, creating an atmosphere of trust and mutual respect and foster-price participation members in decision making. The results showed that the role of leader in performing the function of the legislature parliament in Kapuas Hulu, the reality does not meet expectations. This can be seen from several indicators including: 1) the implementation of the representation function, evident from the many demands / aspirations of the people who submitted to this institution, during the period from 2009 to 2012 many cases have not been resolved, 2) implementation of the legislative function, look The resulting legal product Kapuas Hulu Regency period 2009-2014 still relatively low. 3) implementation of the monitoring function that is owned by the Kapuas Hulu Regency to date has not done as expected. It can be seen, among others, in the areas of policy outputs that better reflect the actual product than the government agency wishes of the people through their representatives, while the approval of the people through parliament more to meet the raw political procedures. Recommendation in this research is the Kapuas Hulu Regency leaders need to give serious attention to the increasing needs of its members in carrying out the functions lagislatif, by the way: look for and choose the ways to satisfy the need to create a pleasant working conditions, reassess the unmet needs, such as safe working conditions and reward are balanced and take action against the firm for its members who break the rules as well as to evaluate the performance achieved its members.Keywords: Leadership Council, Legislative Function.